Dysregulation of Autoantigen Genes in ANCA-Associated Vasculitis Involves Alternative Transcripts and New Protein Synthesis - McInnis, Elizabeth A. (J Am Soc Nephrol, 2015)
Proteinase 3 (PR3) and myeloperoxidase (MPO) are two major autoantigens in patients with vasculitis with ANCA. The genes encoding these autoantigens are abnormally expressed in peripheral granulocytes of patients with active ANCA-associated vasculitis. This study provides evidence that this transcriptional dysregulation results in a variety of mRNA processing events from the PRTN3 gene locus. In addition to elevated levels of PR3 message, leukocyte RNA from patients contained PR3 transcripts with an alternative 3′ untranslated region. Furthermore, we detected usage of an alternative transcription start site within intron 1 of the PRTN3 gene locus that coincided with active disease (odds ratio, 3.3; 95% confidence interval, 1.3 to 8.4; P=0.01). This promoter may be developmentally regulated, because it was active in normal human bone marrow, multiple leukemia cell lines, MCF-7 cells, and subjects after GM-CSF treatment but not subjects with a neutrophil left shift. This transcript, which lacks exon 1 of PRTN3, encodes a 24-kD protein (p24(PR3/MBN)) with a sequence similar to that previously described for myeloblastin. Notably, PR3, p24(PR3/MBN), and MPO were synthesized in cultured neutrophils from patients with active ANCA-associated vasculitis, indicating that increased transcription results in newly synthesized autoantigens in peripheral neutrophils of patients. The synthesis of p24(PR3/MBN) seems to expand the autoantigen repertoire, because immunoblots showed that sera from patients recognized p24(PR3/MBN). These findings emphasize the importance of transcriptional dysregulation of the autoantigen in autoimmune disease.